Monitoring fatigue status in elite soccer players - Thorpe, R. T. (2015)
The physical demands of soccer players competing in the English Premier League have significantly increased in recent years (Barnes et al. 2014; Bush et al. 2015). Elite soccer players are required to compete on a weekly and often bi-weekly basis during a 9-month competitive season. During periods of fixture congestion, players may participate in three matches within a 7-day period. Previous researchers have reported that some components of performance and physiological measures may still be below a pre-match baseline 72 hours following match-play (Mohr et al., 2003; Andersson et al., 2008; Ispirlidis et al., 2008; Fatouros et al., 2010). Nevertheless, data are sparse for the quantification of player fatigue status during competitive periods. Therefore, the primary aim of this thesis is to evaluate potential indicators of fatigue which may be easily measured and utilised in elite soccer.\ud The aim of the first study (Chapter 4) was to quantify the test-retest reliability of a range of potential fatigue variables in elite soccer players. During the pre-season period, resting perceived ratings of wellness (fatigue, muscle soreness, sleep quality and stress), counter-movement jump height (CMJ), sub-maximal heart rate (HRex), post-exercise heart rate recovery (HRRbpm and HRR%), heart rate variability (rMSSD and LnrMSSD) and salivary immunoglobulin-A (S-IgA) were measured during the morning on two consecutive non-training days in thirty-five English Premiership players. Mean values of perceived ratings of wellness (7-13 %CV), CMJ (4 %CV) HRex (3 %CV) and HRR% (10 %CV) were not substantially or statistically significantly different between days. HRV measures` rMSSD (28 %CV) and Ln rMSSD (10 %CV), perceived ratings of sleep (CV 13%CV) and S-IgA (63 %CV) were statistically significantly different between days. All morning-measured fatigue variables with the exception of S-IgA were reliable enough to allow feasible sample sizes in future pre/post studies. These data indicate that the use of perceived ratings of wellness, CMJ, HRR%, and, to a certain extent, HRV (Ln rMSSD) are reliable enough to monitor the fatigue status of a sample of elite soccer players.\ud The aim of the second study (Chapter 5) was to quantify the relationship between daily training load and a range of potential measures of fatigue in elite soccer players during an in-season competitive phase (17-days). Total high-intensity running (THIR) distance, perceived ratings of wellness (fatigue, muscle soreness, sleep quality), CMJ, HRex, HRR% and heart rate variability (Ln rMSSD) were analysed during an in-season competitive period (17 days). Within-subject fluctuations in fatigue (r=-0.51; large; P<0.001), Ln rMSSD (r=-0.24; small; P=0.04), and CMJ (r=0.23; small; P=0.04) were significantly correlated with fluctuations in THIR distance over the study period. Correlations between variability in perceived muscle soreness and sleep quality and HRR% and THIR distance were negligible and not statistically significant. Perceived ratings of fatigue and heart rate variability were sensitive to daily fluctuations in THIR distance in a sample of elite soccer players. Therefore, these specific markers show particular promise as simple, non-invasive assessments of fatigue status in elite soccer players during a short in-season competitive phase. \ud The aim of the third study (Chapter 6) was to determine whether the sensitivity of a range of potential fatigue measures studied in Chapter 5 would be improved compared with the training load accumulated over the previous two, three or four days during a short in-season competitive period (17-days). Fluctuations in fatigue (r=-0.28-0.51; "small" to "large"; p<0.05) were correlated with fluctuations in THIR distance accumulation (1-4-day). Changes in HRex (r=0.28; small; p= 0.02) was correlated with changes in 4-day THIR distance accumulation. Fluctuations in Ln rMSSD (r=-0.24; small; P=0.04), and CMJ (r=0.23; small; P=0.04) were only sensitive to changes in THIR distance for the previous day (Chapter 5). Correlations between variability in muscle soreness, sleep quality and HRR% and THIR distance were negligible and not statistically significant for all accumulation training loads. Perceived ratings of fatigue were sensitive to daily fluctuations in acute THIR distance accumulation although sensitivity attenuated over time. Therefore, the present findings indicate that the sensitivity of morning-measured fatigue measures to changes in training load is not improved when compared with training loads beyond the previous days training.\ud The fourth and final aim of the thesis was to quantify the mean daily changes in training load and parallel changes in measures of fatigue across typical in-season training weeks in elite soccer players. The training load of 29 elite soccer players was measured using the ratings of perceived exertion approach. Perceived ratings of wellness (fatigue, sleep quality and muscle soreness), sub-maximal heart rate (HRex), post-exercise heart rate recovery (HRR) and variability (HRV) were also recorded across training weeks in the in-season competitive period. Morning-measured perceived ratings of fatigue, sleep quality and muscle soreness tracked the changes in RPE-TL, being 35-40% worse on post-match day vs pre-match day (P<0.001). Perceived fatigue, sleep quality and muscle soreness improved by 17-26% from post-match day to three days post-match with further smaller (7-14%) improvements occurring between four days post-match and pre-match day (P<0.01). There were no substantial or statistically significant changes in HRex, HRR% and HRV over the weekly cycle (P>0.05). Morning-measured perceived ratings of fatigue, sleep quality and muscle soreness are clearly more sensitive than HR-derived indices to the daily fluctuations in session load experienced by elite soccer players within a standard in-season week. \ud The results of this thesis have shown that simple, ratings of perceived wellness are reliable and sensitive to short training and competition phases and thus may be a suitable strategy for practitioners to use in the attempt to establish fatigue status in elite soccer players. In particular, this thesis has demonstrated that the greatest sensitivity was observed on a daily basis and during typical training weeks and not during short term load accumulation. . Future work is required to quantify whether perceived ratings of wellness and vagal-related heart rate responses are sensitive to changes in training and match load across an entire competitive season in elite soccer players